AB0010 Flow cytometry and pcr-sso in the determination of hla-b27 in the daily practice. (23rd January 2014) - Sanchez, M.; Bermejo, V.; Serrano, C.; Gonzalo, R.; Castañon, S.; Calabia, O.; Llorente, P.; Sanchez, O.; Garcia, R.
Abstract : Background: The determination of HLA-B27 antigen is a useful tool in the diagnosis of different inflammatory rheumatic diseases, being the association with ankylosing spondylitis (AS) the most frequent. The techniques used for this determination are microlymphocytotoxicity test, flow cytometry assay (FCM) and polymerase chain reaction sequence-specific oligonucleotide (PCR-SSO), being the last one the most accurate determination. Objectives: As FCM rends some indeterminate results, the objective of the present work is to identify by PCR-SSO, the alleles of HLA-B gene that give indeterminate results in FCM. Also, to study the most common diagnosisassociated with HLA-B27 in our cohort of patients. Methods: In 1110 samples from patients studied in the Rheumatology Unit of Fundación Jiménez Díaz-Capio during a year, the determination of HLA-B27 was performed in whole peripheral blood by FCM in a FACS Canto II cytometer (BD Biosciences, USA), using two different monoclonal antibodies: HLA-B27 (FITC) / HLA-B7 (PE) from Beckman Coulter and HLA-B27 (FITC) from One Lambda. Grafics were analyzed with Infinicyt software (Cytognos, Spain) The HLA-B27 typing was performed by PCR-SSO (INNO-LIPA, HLA-B Innogenetics, Belgium). Results: 13, 4% (149) of patients were positive HLA-B27 by FCM. 1, 9% (22) patients that were indeterminate by FCM were evaluated by PCR-SSO. Of these 22 patients, 12, 8% (5) were HLA-B27 positive. The frequency of alleles found in HLA-B27 negative by PCR-SSO were: B44 (20, 5%), B18 (10, 3%), B35 (10, 3%), B8 (7, 7%), B51 (7, 7%), B7 (5, 1%), as well as B15, B37 and B49. Only 18% of HLA-B27 positive patients were diagnosed of ankylosing spondylitis (AS) followed by 14% with undifferentiated spondyloarthropathy, 12% with some type of pains, 9% with arthritis (inflammatory, microcrystalline or infectious), 8% of uveitis and the rest of patients with a miscellaneous. Conclusions: The more frequents alleles of HLA-B that give indeterminate results in the determination of HLA-B27 by FCM, were B44 allele, B18 and B35. FCM is proposed as a useful assay in the screening of the HLA-B27 antigen in the daily practice due its high performance (98, 01%). For borderline cases, PCR-SSO is the recommended tool. References: A high-resolution polymerase chain reaction-sequence-specific primer HLA-B*27 typing set and its application in routine HLA-B27 testing. Downing J, Coates E, Street J, Hammond L, Rees TJ, Pepperall J, Darke C.Genet Test. 2006 Summer;10(2):98-103. Disclosure of Interest: None Declared